Effect of Plasma Exchange on Hepatitis B‐Related Acute‐On‐Chronic Liver Failure: A Cross‐Sectional Study - Lu Wang; Lu Song; Jie Yang (Health Science Reports)
ABSTRACT Background To evaluate the effect of plasma exchange (PE) on the prognosis of patients with hepatitis B virus‐related acute‐on‐chronic liver failure (HBV‐ACLF). Methods The basic information (gender, age, blood type), the frequency and dosage of PE, the changes of indicators before and after PE, the adverse reactions related to PE and the prognosis of patients with HBV‐ACLF who received PE in our hospital from April 2018 to December 2021 were retrospectively analyzed. Results 197 patients with HBV‐ACLF who underwent PE were included in the analysis. Multivariate analysis shows that blood ammonia, ALBI, bacterial infection rate, HBV‐DNA load, MELD score, etc., are independent risk factors affecting the efficacy of PE treatment in HBV‐ACLF patients before and after PE treatment. Conclusion There are many factors influencing the efficacy of plasma exchange in patients with HBV‐ACLF. Compared to other factors, high blood ammonia levels and high ALBI are the independent risk factors for poor short‐term efficacy of plasma exchange.